2015
DOI: 10.1177/1071100715581449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Outcome of Hallux Valgus Surgery

Abstract: Level III, retrospective comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
1
22
1
1
Order By: Relevance
“…6 The modified McBride soft tissue procedure was also performed in all patients, involving release of the adductor hallucis from the proximal phalanx, release of the lateral sesamoid-phalangeal ligament, lateral capsulotomy, and medial capsular imbrication after excision of the bunion. 4,15 Under the same anesthesia setting, an Akin osteotomy would also be done for patients with associated hallux valgus interphalangeus more than or equal to 10 degrees. A staple was used to fix the proximal phalanx medial closing wedge osteotomy.…”
Section: Methodsmentioning
confidence: 99%
“…6 The modified McBride soft tissue procedure was also performed in all patients, involving release of the adductor hallucis from the proximal phalanx, release of the lateral sesamoid-phalangeal ligament, lateral capsulotomy, and medial capsular imbrication after excision of the bunion. 4,15 Under the same anesthesia setting, an Akin osteotomy would also be done for patients with associated hallux valgus interphalangeus more than or equal to 10 degrees. A staple was used to fix the proximal phalanx medial closing wedge osteotomy.…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations were mentioned in the literature regarding different orthopaedic surgeries. Chen et al reported a sevenfold increase in repeat surgery due to obesity in their two year postoperative studies [21]. It is questionable, however, whether the phenomenon occurred regardless of the enrolment of diabetic patients in their study or because of it.…”
Section: Discussionmentioning
confidence: 95%
“…Stewart et al suggested that significant correlation of SSI incidence and diabetes mellitus can be obtained with a higher-power study [6]. Conversely, Chen et al observed no difference in complication rate when assessing the presence of diabetes mellitus (DM) or BMI [21]. Wukich suggested that the higher SSI rate in diabetic patients decreases if the disease is well managed [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…En la cirugía de pie y tobillo la literatura al respecto es escasa. Destaca el trabajo de Chen et al (17) , que valora el efecto de la obesidad tras la cirugía del hallux valgus. Estos autores concluyen que los pacientes obesos y no obesos tiene resultados comparables en términos de función y dolor tras 2 años de la cirugía de hallux valgus.…”
Section: Discussionunclassified